The in vitro assessment of anti proliferation activity of crude diethyl ether extract of Dendrophthoe species against to myeloma culture cell - Mochamad Lazuardi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Herb medicine have an active substances that can dissolved on polar, semi polar and non polar liquid extract. The methanol and ethyl acetate as a polar and semi polar extract liquid were used to study of herb medicine such as Dendrophthoe species. Diethyl ether as a non polar liquid extract was never use to study the Dendrophthoe species. The aim of this study was to investigate the anti proliferation activity of Dendrophthoe species to myeloma culture cells after extracted by non-polar extract solution (diethyl ether). The post test only control group design was used for this research. A thirty six of microtiterplates wells were used for myeloma culture cells in RPMI medium. The wells were devided placing in two groups: treatment groups and controls groups. Each three wells of six treatment subgroups added with 100 µl of 1.1; 5.5; 11; 22; 33 and 44 µg/ml crude diethyl ether extract series. A RPMI solution at similar method and volume were used as control substances. The cells were assessed by inverted microscope in 200x magnified two days after. The cells were quantified analyzed for anti proliferation activity by using 1:1 methylene blue solution. The results showed that started from 11.0 µg/ml of crude diethyl ether extract of Dendrophthoe species have been anti proliferation abilities of myeloma culture cells (p<0.05). In conclusion, actives substances of Dendrophthoe species where dissolved in non polar liquid as diethyl ether has anti proliferation activities to cancer cell in vitro.